2019
DOI: 10.3390/ani9110911
|View full text |Cite
|
Sign up to set email alerts
|

Humanely Ending the Life of Animals: Research Priorities to Identify Alternatives to Carbon Dioxide

Abstract: Simple SummaryCarbon dioxide is commonly used for stunning animals prior to killing. It allows several animals to be killed at once, reduces the need for handling, and is a reliable method. However, research in laboratory rodents, poultry, and pigs has indicated that it causes considerable aversion at concentrations above ambient conditions. Currently, there are no available alternatives with desirable characteristics. This manuscript describes a list of research priorities to find and implement the use of alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 159 publications
(277 reference statements)
1
46
0
Order By: Relevance
“…Inhalant anesthetics are commonly administered to induce general anesthesia for procedures, such as surgery, as well as for euthanasia. It is well-established that rats find CO 2 aversive and potentially painful, leading to calls for refinements and alternative killing methods [3,[7][8][9][13][14][15][16][17][18][19][20][21]. Nevertheless, it remains popular and is used more frequently for killing than inhalant anesthetics because it is practical, easy to use, relatively safe for personnel and is a common procedure with established methods [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…Inhalant anesthetics are commonly administered to induce general anesthesia for procedures, such as surgery, as well as for euthanasia. It is well-established that rats find CO 2 aversive and potentially painful, leading to calls for refinements and alternative killing methods [3,[7][8][9][13][14][15][16][17][18][19][20][21]. Nevertheless, it remains popular and is used more frequently for killing than inhalant anesthetics because it is practical, easy to use, relatively safe for personnel and is a common procedure with established methods [4,14].…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide is widely used in the swine industry with automated gas chambers designed for on-farm use, typically using a fill flow rate of 25% of the chamber volume per minute (half-life 2:46). However, CO 2 is aversive to pigs [5,6] and is a welfare concern [7]. Research in our laboratory [6] found that pigs exposed to CO 2 squealed and flailed when concentrations of CO 2 reached about 20%, which was interpreted as an aversive response.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Conservation Welfare paradigm, progressing more peaceful coexistence also involves: prioritizing research that aims to find methods with fewer welfare impacts, including strategic funding of such research [34,92,93]; and systematically exploring the relative harms associated with existing approaches to facilitate application of those that cause least harm [40,87,91]. Importantly, the harms and benefits of novel approaches to controlling unwanted animals should be systematically evaluated before approval and implementation to determine whether they are genuinely more humane than existing methods (see Responding to new technologies for Conservation below).…”
Section: Peaceful Coexistencementioning
confidence: 99%
“…In contrast, many Conservation Welfare scientists accept some such harm if the outcomes facilitate convincing arguments for the need to protect animals in the future from situations that cause those unpleasant experiences. As an example, collation of historical research on the ability of non-human mammals to experience unpleasant breathlessness reviewed by [115]) now allows us to strongly advocate against the use of stunning methods that cause such experiences [92,93]. Animal welfare scientists and others also work towards minimizing the harms experienced by animals subjected to such research [45,120,121] and we should continue to do so and to push for stronger requirements to safeguard the welfare of research animals [44].…”
Section: First Do No Harm: Similarities and Differencesmentioning
confidence: 99%